(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
The purpose of this study was to investigate Teachers and Educational Administration Preparedness for Implementation of the Integrated HIV/AIDS Education in Public Primary Schools in Kisumu Town, Kenya. The study adopted an expost-facto survey study design. The study area was Kisumu Municipality with the target population being 114 public primary schools. Thirteen schools (13) representing 10% of public primary schools in the municipality were sampled for the study. The Municipal Education Officer, Quality Assurance and Standards Officer, head teachers and the Teacher in Charge were selected each purposively for the study. Teachers who participate in the implementation of the programme were simple sampled randomly; two (2) from each school giving 26 (50%) teacher respondents. A ratio of 10% percent was used to arrive at the number of pupil respondents in each school. Data were gathered through questionnaires, interview schedule and observation checklist. Quantitative and qualitative data analysis techniques were utilized. Data from questionnaires were analyzed in frequencies and percentages using SPSS. The major findings of the study indicate that a majority 28 (53.8%) of the respondents claimed that they had not undergone training in HIV education and 40 (76.9%) of the respondents said that they had never attended a seminar on HIV/AIDS. The study recommends careful selection of media among the available resources for effective teaching and learning process in HIV/AIDS education.